PENGARUH PEMASARAN EKSPERIENSIAL TERHADAP RETENSI PELANGGAN PADA PENGUNJUNGRESORT&SPA KAMPUNG SAMPIREUN GARUT :Survei pada Pengunjung Resort&Spa Kampung Sampireun Garut - Irna Widiastuti, - (2009)
Business sector character hospitallity area industry that include business travel, tourism and hotel gives market opportunity enough vast so that push to stand it various tourism tool effort likes hotel (resort). Appearance resort at Garut city with various facilities and product/service tender that interesting to evoke rivalry enough tight because push consumer to move, so that there is no binding that determine troth/loyalty level. various strategy applieds to defend customer (retention) so that loyal permanent and customer retention more increase. One of strategy or efforts defends when does experience creation unique and leave an impression at every interaction with customer as distinctive brand companies that is pass to approach emotional by applying experiencial marketing. Watchfulness aims to detect marketing description eksperiensial that consist of sense, feel, think, act and relate towards customer retention. Object in this watchfulness customer resort&spa Kampung Sampireun Garut. free variable in this watchfulness experiencial marketing (X). While bound variable in this watchfulness customer retention (Y). Watchfulness kind that used descriptive verifikatif, and method that used explanatory survey with technique systematic random sampling, and sample total 60 respondents. Data analysis technique that used stripe networ (path analysis) by means of help computer software spss 15.0. Data that used primary data and secondary with collecting technique passes interview with staff resort, direct observation to resort&spa Kampung Sampireun Garut, watchfulness inquiry distribution, and literature study. Based on hypothesis testing, experiencial marketing has influence towards customer retention, with the meaning more gooder experiencial marketing so also customer retention at resort&spa Kampung Sampireun Garut